New wild-type isolates of the nematode genera Oscheius, Alloionema, and a different rhabditid genus (Nematoda: Rhabditida) found in forests of Vietnam - Huan, Ha Van; Son, Le Tho (Vietnam Journal of Biotechnology, 2024)
In this report, we describe the isolation and determination of four new free-living nematode (FLN) strains of three species in different nematode genera (Oschieus, Alloionema, and another rhabditid genus) from Cat Tien and Cuc Phuong National Parks, Vietnam using the isolation protocol for Caenorhabditis nematodes. Of the four strains, three strains were similar to the previous determinants and one strain may be a new rhabditid species that was first found in Vietnam. They can grow well on the E. coli OP50 – seeded media (New Cheap Media No. 18 (NcM18) and Nematode Growth Media (NGM)). Compared with the isolation of the Caenorhabditis nematodes in the same scenario, the frequencies of finding these three genera were low because of the inappropriate isolation method employed in the Caenorhabditis nematodes. This data supports knowledge of the FLN diversity and implies that FLNs that stay uncovered in the forestry ecosystems should be uncovered using different isolation methods for the nematode order Rhabditida, i.e. entomopathogenic nematodes (EPNs), helminths, and the superfamily Rhabditidae.